Sosialisasi Tatacara Penyusunan Qanun Gampong untuk Aparatur Gampong Panton Beunot Kabupaten Pidie - Marzuki; Junaidi; Media, M. Agmar (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2025)
This community service activity aims to improve the understanding and skills of the Panton Beunot Village apparatus, Pidie Regency, in designing and compiling the Village Qanun. Qanun is a village-level regulation that is important as a legal basis for organizing the social life of the community. The implementation of this activity includes socialization, technical guidance, and assistance in drafting the Qanun, especially the Qanun on Village Order and Security. The methods used are lectures, focus group discussions (FGD), and direct training for village apparatus. The results of the activity show an increase in the knowledge and skills of the apparatus in the legislative process at the village level. This activity also succeeded in producing a Qanun draft that is relevant to local problems, such as disturbances of order, violations of customary and religious norms, and environmental preservation. This activity is an important initial step in strengthening participatory and law-based village governance.